Immobilization of chitinase on charcoal improves ability of enzyme to hydrolyze chitin - Jenan Atiyah Ghafil (World Journal of Experimental Biosciences, 2013)
The chitinase is an enzyme has a good ability to hydrolyze chitin in nature. Thus this enzyme plays an important role in clean the environments and in industries. The activity of the free chitinase to catalyze the chitin was evaluated in previous study. The activity of immobilized chitinase on charcoal was not studied previously. In current study, the activity of immobilized chitinase to hydrolyze chitin was studied. Purified chitinase was immobilized on charcoal then the activity of immobilized was checked and compared with activity of free chitin. The results showed that the activity of immobilized chitinase was significantly higher than the activity of free chitinase. The activity of immobilized chitinase was checked at different physical conditions like pH and temperature. Maximum enzyme activity to hydrolyze chitin was observed at pH 8 and temperature 40 OC. The present study showed that the activity of chitinase increased when the enzyme was immobilized on charcoal.
Keywords: Charcoal; Chitin; chitinase; Immobilization.